Evaluation of kidney allograft status using novel ultrasonic technologies - Cheng Yang; Mushuang Hu; Tongyu Zhu; Wanyuan He (Asian Journal of Urology)
Early diagnosis of kidney allograft injury contributes to proper decisions regarding treatment strategy and promotes the long-term survival of both the recipients and the allografts. Although biopsy remains the gold standard, non-invasive methods of kidney allograft evaluation are required for clinical practice. Recently, novel ultrasonic technologies have been applied in the evaluation and diagnosis of kidney allograft status, including tissue elasticity quantification using acoustic radiation force impulse (ARFI) and contrast-enhanced ultrasonography (CEUS). In this review, we discuss current opinions on the application of ARFI and CEUS for evaluating kidney allograft function and their possible influencing factors, advantages and limitations. We also compare these two technologies with other non-invasive diagnostic methods, including nuclear medicine and radiology. While the role of novel non-invasive ultrasonic technologies in the assessment of kidney allografts requires further investigation, the use of such technologies remains highly promising.